2021
DOI: 10.1021/acs.jpcc.0c09746
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Platinum Nanoparticles by Plasma Sputtering onto Glycerol: Effect of Argon Pressure on Their Physicochemical Properties

Abstract: Electrochemical energy conversion devices, such as polymer electrolyte membrane fuel cells (PEMFCs) and PEM electrolyzers are considered as possible candidates for integration in future renewable energy network 1,2 . However, the oxygen reduction reaction (ORR) kinetic at the cathode of a PEMFC is slow and the overpotential at the cathode is generally high (higher than 0.200 V), whereas that of the hydrogen oxidation at the anode is ca. 0.050 V 3 . For this purpose, platinum (Pt) or its alloys are often req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…However, some scientists reported an increase in the NP size with discharge voltage (Suzuki et al, 2009;Wender et al, 2010Wender et al, , 2011Sugioka et al, 2015). This behavior might be explained by the heating of the host liquid by plasmaborn species and sputtered metal atoms and the IR radiations emitted by the target during the deposition (Orozco-Montes et al, 2021). For example, it has been recently shown that the temperature of 4 ml of glycerol was increased by 17°C during 20 min platinum deposition with 12 cm of working distance (100 W; 5 W/cm 2 ) and by 40°C with 5 cm of working distance at the same DC power density (Orozco-Montes et al, 2021).…”
Section: Effect Of Sputter Powermentioning
confidence: 99%
See 2 more Smart Citations
“…However, some scientists reported an increase in the NP size with discharge voltage (Suzuki et al, 2009;Wender et al, 2010Wender et al, , 2011Sugioka et al, 2015). This behavior might be explained by the heating of the host liquid by plasmaborn species and sputtered metal atoms and the IR radiations emitted by the target during the deposition (Orozco-Montes et al, 2021). For example, it has been recently shown that the temperature of 4 ml of glycerol was increased by 17°C during 20 min platinum deposition with 12 cm of working distance (100 W; 5 W/cm 2 ) and by 40°C with 5 cm of working distance at the same DC power density (Orozco-Montes et al, 2021).…”
Section: Effect Of Sputter Powermentioning
confidence: 99%
“…This behavior might be explained by the heating of the host liquid by plasmaborn species and sputtered metal atoms and the IR radiations emitted by the target during the deposition (Orozco-Montes et al, 2021). For example, it has been recently shown that the temperature of 4 ml of glycerol was increased by 17°C during 20 min platinum deposition with 12 cm of working distance (100 W; 5 W/cm 2 ) and by 40°C with 5 cm of working distance at the same DC power density (Orozco-Montes et al, 2021). An increase in liquid temperature leads to a decrease in both the viscosity and surface tension of the host liquid, so that the sputter atoms more easily penetrate under the liquid surface and the number of collisions between freshly solvated sputtered atoms and primary clusters formed under the liquid surface increases.…”
Section: Effect Of Sputter Powermentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of elements has been successfully sputtered onto liquids to create monometallic NPs, including Au [12, 114, 115, 118, 120, 122, 125, 126, 129, 132, 134, 138, 139, 142, 143, 145 -149, 153, 167, 174 -176, 180 -183, 188, 189, 203,204,207,208,210,211,214,216,218,229-238], Ag [11,118,119,123,131,164,175,179,184,185,188,196,205,206, 217, 218, 231-233, 239], Cu [150,155,164,188,189,198,210,230,240,241], Pt [121,133,163,168,169,186,[242][243][244][245], Pd [116,212,231,242,246,247], Fe [11,161,162], In [187], Ni [135] and Mo [20...…”
Section: Monometallic Npsmentioning
confidence: 99%
“…Figure 8: TEM images and corresponding size distributions of Pt NPs produced via MS of a platinum target onto glycerol at pressures of 1, 4, and 9 Pa, respectively.Figure8was reprinted with permission from[163]. Copyright 2021 American Chemical Society.…”
mentioning
confidence: 99%